2005
DOI: 10.1590/s0100-879x2005000800010
|View full text |Cite
|
Sign up to set email alerts
|

Some physico-chemical parameters that influence proteinase K resistance and the infectivity of PrP Sc after high pressure treatment

Abstract: Crude brain homogenates of terminally diseased hamsters infected with the 263 K strain of scrapie (PrP Sc ) were heated and/or pressurized at 800 MPa at 60ºC for different times (a few seconds or 5, 30, 120 min) in phosphate-buffered saline (PBS) of different pH and concentration. Prion proteins were analyzed on immunoblots for their proteinase K (PK) resistance, and in hamster bioassays for their infectivity. Samples pressurized under initially neutral conditions and containing native PrP Sc were negative on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous works have shown a strong reduction in the infectivity of scrapie prions as a function of pressure and heat (Fernandez Garcia et al, 2004;Heindl et al, 2005;Heindl, Fernandez Garcia, Butz, Pfaff & Tauscher, 2006) also associated to a decrease on the PK resistant fraction detected on immunoblots. Here the kinetic parameters governing the pressure inactivation of the 263K strain of scrapie were studied.…”
Section: Kinetics Of Scrapie Prion Inactivationmentioning
confidence: 88%
“…Previous works have shown a strong reduction in the infectivity of scrapie prions as a function of pressure and heat (Fernandez Garcia et al, 2004;Heindl et al, 2005;Heindl, Fernandez Garcia, Butz, Pfaff & Tauscher, 2006) also associated to a decrease on the PK resistant fraction detected on immunoblots. Here the kinetic parameters governing the pressure inactivation of the 263K strain of scrapie were studied.…”
Section: Kinetics Of Scrapie Prion Inactivationmentioning
confidence: 88%
“…Moreover, although some studies have shown that digestion with a protease in the presence of denaturing agents is sufficient to eliminate the infectivity of prion (22), others suggested a difference between the removal of immunoreactive material and infectivity (23)(24)(25)(26)(27). Alternatively, residual infectivity may be found in the portion of PrP Sc not recognized by SAF83.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Prof. Bernhard Tauscher (Federal Research Center on Nutrition & Food, Karlsruhe, Germany) discussed results showing that food of high sensory quality and statistical sterility was produced by the combination of pressure and temperature, while most of the vitamins, peptides, food additives, metal ions, and compounds relevant for the sensory characteristics of food products were preserved. As an additional result, it was suggested that the effects of pressure on the prion protein might be an interesting methodology to prevent contamination by foodborne prion protein, since high hydrostatic pressure induces structural changes in the prion protein that make it susceptible to proteases (19).…”
Section: The Conference On High Pressure Bioscience and Biotechnologymentioning
confidence: 99%